Lippia javanica (Burm. F.) Herbal Tea: Modulation of Hepatoprotective Effects in Chang Liver Cells via Mitigation of Redox Imbalance and Modulation of Perturbed Metabolic Activities - Salau, Veronica F.; Erukainure, Ochuko L.; Olofinsan, Kolawole A.; Schoeman, Recardia L. S.; Matsabisa, Motlalepula G. (Frontiers in Pharmacology, 2023)
Hepatic oxidative injury is one of the pathological mechanisms that significantly contributes to the development of several liver diseases. In the present study, the hepatoprotective effect of Lippia javanica herbal tea was investigated in Fe 2+ -mediated hepatic oxidative injury. Using an in vitro experimental approach, hepatic oxidative injury was induced by co-incubating 7 mM FeSO4 with Chang liver cells that have been pre-incubated with or without different concentrations (15-240 μg/mL) of L. javanica infusion. Gallic acid and ascorbic acid served as the standard antioxidants.The infusion displayed a reducing antioxidant activity in ferric-reducing antioxidant power (FRAP) assay and a potent scavenging activity on 2,2-diphenyl-2-picrylhydrazyl (DPPH) radical.Pretreatment with L. javanica infusion significantly elevated the levels of reduced glutathione and non-protein thiol, and the activities of superoxide dismutase (SOD) and catalase, with concomitant decrease in hepatic malondialdehyde levels, acetylcholinesterase, glucose-6-phosphatase, fructose-1,6-bisphosphatase, glycogen phosphorylase and lipase activities. The infusion showed the presence of phytoconstituents such as phenolic compounds, tannins, phenolic glycosides and terpenoids when subjected to liquid chromatography-mass Spectrometry analysis. Molecular docking revealed a strong binding affinity of dihydroroseoside and obacunone with both SOD and catalase compared to other phytoconstituents. These results portray a potent antioxidant and hepatoprotective effect of L. javanica, which may support the local usage of the herbal tea as a prospective therapeutic agent for oxidative stress-related liver diseases.